Pabrik Bulu Mata Palsu dan Ruang Kuasa Perempuan Buruh (Kajian Etnografis di Desa Pasunggingan, Kecamatan Pengadegan, Kabupaten Purbalingga, Jawa Tengah) - Nurlaili Khikmawati (UIN Siber Syekh Nurjati Cirebon, 2020)
The study regarding women labor is always interesting to done. This is due to the domestic roles of women that women labor has a double burden for work in the factory and work in the household/domestic area. In addition, the placement of women in the domestic area makes